DELINEATION OF UNCERTAINTIES IN ANISOTROPIC SHALLOW SUBSURFACE BY INTEGRATED GEOPHYSICAL AND GEOMECHANICAL EXAMINATION (Pakistan Journal of Science, 2020)
This study focused on geophysical and geomechanical analyses to arbitrate weak zones in Limestone of Gaj formation. Two boreholes were drilled and used to facilitate downhole seismic experiment down to 30 meters of depth. The downhole seismic method was supplied compressional waves velocities for inspection of shallow subsurface properties to evaluate local site condition. The primary data of P-waves velocities are varying from 566 m/s to 1225 m/s (BH-1) 570 m/s to 1320 m/s (BH-2). The information of elastic moduli were derived from primary waves data through empirical relationships. The core samples were collected and examined for geotechnical investigation in the laboratory. This study contributes to ensure the engineering strength of the ground and concluded that the ignorance of substrate conditions may lead to instability or construction failure.
Keywords: Downhole seismic; shallow subsurface; foundation surveying; Karachi